Evaluating Pain Education Programs: An Integrated Approach. (2011) - Dubrowski, Adam; Morin, Marie-Paule
Abstract : Evaluation of educational programs and assessment of learning are essential to maintain high-standard health science education, which includes pain education. Current models of program evaluations applied to the education of the health professions, such as the Kirkpatrick model, are mainly outcome based. More recently, efforts have been made to examine other process-based models such as the Context Input Process Product model. The present article proposes an approach that integrates both outcome- and process-based models with models of clinical performance assessment to provide a deeper understanding of a program function. Because assessment instruments are a critical part of program evaluation, it is suggested that standardization and rigour should be used in their selection, development and adaptation. The present article suggests an alternative to currently used models in pain education evaluation.